A Path to High-Value Gastric Cancer Surgery Care Delivery - Swee H. Teh, MD; Sharon Shiraga, MD; Aaron M. Kellem, BS (Math); Robert A. Li, MD; David M. Le, MD; Said P. Arsalane, MSHA; Fawzi S. Khayat, MD; Yan Li, MD; I-Yeh Gong, MD; Jessica M. Lee, MD (Annals of Surgery Open)
Objective:. To evaluate the feasibility, safety, and effectiveness of a comprehensive regional program, including the Minimally Invasive Recovery and Empowerment Care (MIREC) pathway, that can significantly reduce hospital stays after laparoscopic gastrectomy without increasing adverse events. Background:. Cost-effectiveness and improving patient outcomes are crucial in providing quality gastric cancer care worldwide. Methods:. To compare the outcomes of gastric cancer surgery using 2 different models of care within an integrated healthcare system from February 2012 to March 2023. The primary endpoint was the length of hospital stay. The secondary endpoints were the need for intensive care unit care, emergency room (ER) visits, readmission, reoperation, and death within 30 days after surgery. Results:. There were 553 patients, 167 in the pre-(February 2012–April 2016) and 386 in the post-MIREC period (May 2016–March 2023). Perioperative chemotherapy utilization increased from 31.7% to 76.4% (P < 0.0001). Laparoscopic gastrectomy increased from 17.4% to 97.7% (P < 0.0001). Length of hospitalization decreased from 7 to 2 days (P < 0.0001), with 32.1% and 88% of patients discharged home on postoperative day 1 and postoperative day 2, respectively. When comparing pre- and post-MIREC, intensive care unit utilization (10.8% vs. 2.9%, P < 0.0001), ER visits (34.7% vs. 19.7%, P = 0.0002), and readmission (18.6% vs. 11.1%, P = 0.019) at 30 days were also considerably lower. In addition, more patients received postoperative adjuvant chemotherapy (31.4% to 63.5%, P < 0.0001), and the time between gastrectomy and starting adjuvant chemotherapy was also less (49–41 days; P = 0.002). Conclusion:. This comprehensive regional program, which encompasses regionalization care, laparoscopic approach, modern oncologic care, surgical subspecialization, and the MIREC pathway, can potentially improve gastric cancer surgery outcomes. These benefits include reduced hospital stays and lower complication rates. As such, this program can revolutionize how gastric cancer surgery is delivered, leading to a higher quality of care and increased value to patients.